Innovation and Competitiveness of the Republic of Bulgaria During the Period 2007-2017 - Shotarov, Antoan (UNWE Yearbook, 2021)
As a result of the deepening globalization processes of the late 20th and early 21st centuries, competitiveness is perceived as one of the main indicators determining whether a country will maintain its global economic position. The countries of Central and Eastern Europe, including Bulgaria, lagged significantly behind at the beginning of the century in terms of competitiveness compared to the highly developed Western European countries. Innovation is one of the main factors influencing competitiveness. The aim of the study is to analyze the change in the innovation activity and competitiveness of Bulgaria in the period 2007-2017. The study will be developed through empirical and DESK analysis.
Keywords: Competitiveness; European union; Bulgaria; Innovation activity